Work-Life Balance Among Working Mothers in Malaysia - Omar, Muhamad Khalil; Mohd, Idaya Husna; Ahmad, Mohamad Fahimi; Dahalan, Noor Azura (Advances in Social Sciences Research Journal, 2022)
Employees especially working mothers are struggling to accommodate employer’s expectations and fulfilling the demands of their family needs. Achieving work life balance is the dream and hope of almost every working mother. Though many factors affected work life balance, factors like stress management, work culture and employer’s role are believe to be significance variables. A study conducted in the National Sport Council of Malaysia on 100 working mothers reveals the truth of this relationship.